The Relationship Between Sustainable Food House (KRPL) Area Program Activities and Empowerment of Farmer Women - Faqih, Achmad; Aisyah, Siti; Sofiyuddin, Sofiyuddin; Adiyansyah, Sayu; Sawiko, Sawiko; Rusiyanto, Untung (Eduvest - Journal of Universal Studies, 2023)
National food production capacity is constrained by competition in land use, extreme climate change, phenomena of degradation of natural resources and the environment, and limited support for agricultural infrastructure. Therefore, it is necessary to empower agriculture, one of which is the strategy of utilizing yards to support food security and family food self-sufficiency. The study aims to relationship between sustainable food house (KRPL) area program activities and empowerment of farmer women. The study used a quantitative research design with descriptive survey techniques. The research was carried out from May to June 2023 in the Flower Farmer women's group in Grogol Village, Kapetaka District, Cirebon Regency with a total sample of 30 people. Data collection techniques using interview techniques. Research data were analyzed usingSpearman level correlation coefficient test. The results showed 1) there was a significant relationship between the use and arrangement of the yard and the empowerment of female farmers in Grogol Village, Kapetakan District, Cirebon Regency, 2) There was a significant relationship between the development of village nurseries (KBD) and the empowerment of female farmers in Grogol Village, Kapetakan District, Regency Cirebon.